Psychosocial Morbidity Among Doctors Working in Intensive Care Unit in Tertiary Care Hospitals in Chennai - A Cross Sectional Study - P Vinothkumar; Edward, Shanthi; VM, Anantha Eashwar (National Journal of Community Medicine, 2022)
INTRODUCTION: Intensivists routinely works in a demanding, highly complicated environment where mortality and morbidity are common events and errors can lead to series situation in the working place. Doctors and other health care workers used to work in high stressful condition which affects their own physical as well mental health. AIM &OBJECTIVE: The aim was to assess psychological factors such as mood status (anxiety, depression and stress) as well as to find out the various influencing factors on psychological health among doctors working in Intensive Care Unit (ICU). METHODS: The list of tertiary care hospitals in Chennai were collected and Ten hospitals were selected randomly by lottery method and 15 doctors who were working in Intensive Care Units (ICU) were selected from each hospital by systematic random sampling to arrive at the calculated sample size of 150. The Data was collected using the Pretested semi structured questionnaire and validated Depression, Anxiety and Stress (DASS-21) Scale. Data was entered in MS Excel and analysed by SPSS version 22. RESULTS: The prevalence of Depression, Anxiety and Stress was found to be 78.6%, 86% and 60.6% respectively among ICU doctors. It was found that, having a history of either diabetes or hypertension was an important predictor for depression with an adjusted odds ratio of 3,48 (95% CI – 1.3-8.8) and person who were working more than 8 hours per day was statistically associated(p<0.05) with stress with an adjusted odds ratio of 2.21 (95% CI – 1.1-5.49). CONCLUSIONS: Routine screening of physical health and mental health for doctors involved in the diagnostic as well as treatment aspects of work towards patients in Intensive Care Unit (ICU) should be conducted periodically.